2010
DOI: 10.1094/pdis-94-8-1026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Phytophthora cinnamomi with White Oak Decline in Southern Ohio

Abstract: A decline syndrome and widespread mortality of mature white oak tree (Quercus alba) associated with wet and low-lying areas has been recently observed in southern Ohio forests. Previous studies have isolated Phytophthora cinnamomi from white oak rhizospheres. In 2008 and 2009, P. cinnamomi population densities in two healthy and two declining white oak stands at Scioto Trail State Forest were quantified and potential roles of three environmental drivers of Phytophthora spp.–induced decline were assessed: soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Furthermore, the isolates were nearly equally aggressive, a testament to the virulence of the P. cinnamomi population in eastern U.S. forests. Other studies have also shown the pathogenicity of P. cinnamomi isolates from the eastern United States on various oak trees (6, 30,46) and, similar to our findings, little variation existed in aggressiveness of P. cinnamomi (18,61). Although little difference in pathogenicity was detected among the isolates, variation was found when seedling mortality rates were compared.…”
Section: Phytophthora Cinnamomi Isolatessupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the isolates were nearly equally aggressive, a testament to the virulence of the P. cinnamomi population in eastern U.S. forests. Other studies have also shown the pathogenicity of P. cinnamomi isolates from the eastern United States on various oak trees (6, 30,46) and, similar to our findings, little variation existed in aggressiveness of P. cinnamomi (18,61). Although little difference in pathogenicity was detected among the isolates, variation was found when seedling mortality rates were compared.…”
Section: Phytophthora Cinnamomi Isolatessupporting
confidence: 91%
“…In another study, when a white oak forest stand was sampled intensively, CFU levels were seven dmes greater on declining white oak trees than on oak trees without any crown dieback (10). The same conclusion was reached when CFU of declining white oak stands of the same forest site were quantified for 2 years and found to be significantly greater at declining trees than at healthy ones both years (46). The latter study also confinned the field finding in an inoculum doseresponse study using white oak seedlings and showed that greater inoculum levels resulted in significant root damage.…”
Section: Phytophthora Cinnamomi Isolatessupporting
confidence: 69%
See 2 more Smart Citations
“…Phytophthora cinnamomi, P. quercina (an oak-specific species), and several other Phytophthora spp. have been detected in recent decades in Europe (Jung et al, 1999(Jung et al, , 2002Gallego et al, 1999;Vettraino et al, 2002;Balci and Halmschlager, 2003) and in North America (Table 1; Balci et al, 2007Balci et al, , 2010Nagle et al, 2010). Although their role is not yet completely understood, it may be exacerbated by changing climate conditions (reviewed by Brasier, 1996;Jönsson, 2006).…”
Section: Emergent Biotic Agents Involved In Oak Decline: Pathogensmentioning
confidence: 99%